Avaliação da atividade da telomerase em células-tronco de pacientes com displasia cortical de Taylor - Borges, Juliano Viana (2015)
The Cortical dysplasia is one of the most frequent forms of malformations of cortical development, with a condition that causes a large portion of refractory partial epilepsy to drug treatment. This condition is characterized by a heterogeneous group of cortical lesions and can also be described as cortical dysgenesis or neuronal migration disorder. The genetic factors involved in cortical dysplasia, such as the expression of the telomerase enzyme, are not commonly investigated, mainly due to the limited number of cases is the lack of an experimental model. Objective: This study aimed to analyze the activity and the expression of the enzyme telomerase in patients with cortical dysplasia of Taylor, normal fibroblasts, stem cells from umbilical cord tissue and human tumor. Methodology: the activity and expression of hTERT portion of telomerase were evaluated in patient fibroblasts with Cortical Dysplasia of Taylor (n = 1) and compared with control patients fibroblasts (n = 3) and umbilical cord stem cells (n = 3) and human tumor cell line A549 were maintained in culture. The analysis of the hTERT gene was done by PCR and the telomerase activity was measured by TRAP assay that uses real-time PCR. Results: telomerase activity was higher in tumor cells (Ct = 28.32), while in other cell types and other types studied values were similar: control (Ct = 33.73) Umbilical Cord (Ct = 32.88) and dysplasia (Ct = 33.56). The expression of hTERT portion of telomerase was the control group was 2,58x more expressed, the Dysplasia and tumor groups were 61,25x and 635,48x more expressed respectively as the control. Conclusion: The telomerase appeared to be more active and higher expression in the tumor cell line when compared to other cell types surveyed. The hTERT gene was more expressed in the patient Taylor cortical dysplasia than in the other groups and control umbilical cord indicating that telomerase is expressed in most patients with this disease.